2010
DOI: 10.1016/j.tox.2010.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Biological response and morphological assessment of individually dispersed multi-wall carbon nanotubes in the lung after intratracheal instillation in rats

Abstract: Biological responses of multi-wall carbon nanotubes (MWCNTs) were assessed after a single intratracheal instillation in rats. The diameter and median length of the MWCNTs used in this study were approximately 60 nm and 1.5 μm, respectively. Groups of male Sprague-Dawley rats were intratracheally instilled with 0.04, 0.2, or 1 mg/kg of the individually dispersed MWCNT suspension. After instillation, the bronchoalveolar lavage fluid was assessed for inflammatory cells and markers, and the lung, liver, kidney, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 27 publications
6
62
1
Order By: Relevance
“…The BALF cytokine parameters such as IL-5, IL-6, MCP-1 and GRO/ KC had good correlation to lung inflammation, but not IL-1α, IL-1β, IL-2, IL-4, IL-10, GM-CSF, INF-γ, TNF-α, IL-12, IL-18. Several papers reported usefulness of the BALF analysis on pulmonary damage (Henderson et al, 1985;Henderson, 2005;Kobayashi et al, 2010). Our present study confirmed the usefulness of the BALF for pulmonary toxicity assessment.…”
Section: Resultssupporting
confidence: 88%
“…The BALF cytokine parameters such as IL-5, IL-6, MCP-1 and GRO/ KC had good correlation to lung inflammation, but not IL-1α, IL-1β, IL-2, IL-4, IL-10, GM-CSF, INF-γ, TNF-α, IL-12, IL-18. Several papers reported usefulness of the BALF analysis on pulmonary damage (Henderson et al, 1985;Henderson, 2005;Kobayashi et al, 2010). Our present study confirmed the usefulness of the BALF for pulmonary toxicity assessment.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, the authors did not find any evidence of chronic inflammation, such as angiogenesis or fibrosis, induced by MWNT instillation (Kobayashi et al, 2010). Light microscopic examination indicated that MWNT aggregates deposited in the lungs were phagocytized by alveolar macrophages and were accumulated in the lungs until 6-month post-exposure.…”
Section: Respiratory Exposure: Pulmonary Toxicitymentioning
confidence: 92%
“…Light microscopic examination indicated that MWNT aggregates deposited in the lungs were phagocytized by alveolar macrophages and were accumulated in the lungs until 6-month post-exposure. These aggregates were located in the alveolar or interstitial macrophages, but individual MWNTs were not present in the cells of the interstitial tissue (Kobayashi et al, 2010). However, in the light micrograph panels, provided by the authors (Kobayashi et al, 2010) MWNTs seem to extend outside the macrophages in several directions, which is commonly referred to as incomplete or frustrated phagocytosis that is known to be a proinflammatory condition (Balkwill & Mantovani, 2001).…”
Section: Respiratory Exposure: Pulmonary Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…To prepare a stable suspension, MWCNTs, which were synthesized using a floating catalyst method (Nikkiso Co. Ltd., Japan), were sonicated (180W) for 30 min in an aqueous solution of 0.5 mg ml −1 polyoxyethylene octyl phenyl ether (Triton‐X, Wako Pure Chemical Industries Co. Ltd., Osaka, Japan) using an ultrasonic bath (5510‐MT; Branson Ultrasonics Co., Danbury, CT, USA) according to previously described methods (Kobayashi et al ., 2010; Chen et al ., 2011; Morimoto et al ., 2012). …”
Section: Methodsmentioning
confidence: 99%